The Optimization Design of Six-bar Linkage Mechanism - Xiaoli Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
At present, multi-bar linkage mechanism is one of the most important directions of mechanical presses’ development. Utilizing the typical multi-linkage drawing mechanism of the plunger slide and compounding its parameters scientifically are a fairly effective way to realize the drawing technology demand. This paper established kinematics mode of the six-bar drawing mechanism by bar-group method, and produced simulated system by Visual Basic, which simulated the actual motion of the mechanism. With the objective function-velocity fluctuation in drawing and drawing depth, using chaos genetic algorithm method, carried out optimization design of the mechanism, and acquired several groups’ data. The optimization results showed that their performance in kinematics was improved greatly and had exceeded the original mechanism. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2863